Facile Preparation of Antibacterial Gelatin-Kaolin Bionano- composite Membranes and Study of Water Sorption and Water Vapour Transmission Rate (WVTR). Issue 6 (2nd November 2021) - Shrungi, Manjulata; Goswami, Anjana; Bajpai, Jaya; Bajpai, Anil Kumar
Abstract: Glutaraldehyde crosslinked gelatin kaolin bionanocomposite films were prepared by casting method and characterized by various techniques and water vapour transmission rates and water sorption studies were performed. The FTIR study revealed the interaction between functional groups of gelatin and kaolin evidenced by shifting of some spectral peaks. The grain size of bionanocomposite films was calculated to be 29 nm from XRD analysis and the crystallinity was 62 %. The SEM and AFM analysis suggested for heterogeneous surfaces having pores and pits. The glass transition temperature of gelatin film was found to increase from 70 to 100°C as revealed by DSC technique. The thermal properties increased with increasing kaolin. The addition of kaolin marked an increase in Young's modulus and tensile strength. The bionanocomposite films showed a fall in water sorption capacity with increasing kaolin content. The water vapour transmission rate (WVTR) decreased with increasing addition of kaolin. The films were found to show antibacterial nature against Aureus . GRAPHICAL ABSTRACT: UF0001